A MULTIVARIATE PROGNOSTIC MODEL OF TREATMENT FAILURE AFTER SURGICAL CORRECTION OF VARICOCELE-ASSOCIATED INFERTILITY (Global Conference on Medical and Health Sciences, 2026)
Although varicocelectomy improves semen parameters in most patients, a substantial proportion do not achieve fertility recovery, and there is no validated integral tool that predicts the probability of response before surgery. A multivariate prognostic model would allow objective preoperative stratification and the timely planning of assisted reproduction.